Barriers to early prenatal care in South Africa. - Haddad, Diane N; Makin, Jennifer D; Pattinson, Robert C; Forsyth, Brian W (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2015)
To understand the barriers delaying early prenatal care for women in South Africa.